Can uncertainties in sea ice albedo reconcile patterns of data‐model discord for the Pliocene and 20th/21st centuries?. Issue 6 (20th March 2014) - Howell, Fergus W.; Haywood, Alan M.; Dolan, Aisling M.; Dowsett, Harry J.; Francis, Jane E.; Hill, Daniel J.; Pickering, Steven J.; Pope, James O.; Salzmann, Ulrich; Wade, Bridget S.
Abstract General Circulation Model simulations of the mid‐Pliocene warm period (mPWP, 3.264 to 3.025 Myr ago) currently underestimate the level of warming that proxy data suggest existed at high latitudes, with discrepancies of up to 11°C for sea surface temperature estimates and 17°C for surface air temperature estimates. Sea ice has a strong influence on high‐latitude climates, partly due to the albedo feedback. We present results demonstrating the effects of reductions in minimum sea ice albedo limits in general circulation model simulations of the mPWP. While mean annual surface air temperature increases of up to 6°C are observed in the Arctic, the maximum decrease in model‐data discrepancies is just 0.81°C. Mean annual sea surface temperatures increase by up to 2°C, with a maximum model‐data discrepancy improvement of 1.31°C. It is also suggested that the simulation of observed 21st century sea ice decline could be influenced by the adjustment of the sea ice albedo parameterization.